Lessons learnt in business process reengineering: a case study of an Internet Service provider organisation. - Lau, Ming Chiew. (2008)
The research focus on lessons learnt in implementing a BPR exercise by using a case study of an Internet Service Provider. It examines and reviews methodologies used for BPR and Software Reengineering with the aim to identify typical problems faced and the associated benefits of a successful reengineering project.